Optimizing the Halal Certification System through Community-Based Assistance for Poultry Slaughterhouses - Salmia Salmia; Munawaroh Munawaroh; Mar Atun Saadah; Karlina Rahayu (Universitas Nurul Jadid, 2026)
The limited number of halal-certified poultry slaughterhouses in Indonesia represents a critical bottleneck in strengthening the halal supply chain. Empirical evidence shows that small-scale slaughterhouses often lack halal certification due to low technical capacity, inadequate facilities, and weak managerial systems, which undermine halal traceability and increase compliance risks. This community service aims to strengthen the halal supply chain by enhancing capacity and facilitating halal certification for a poultry slaughterhouse group in Jambi City, selected due to its strategic role as a local supplier and its low initial readiness for certification. This program applied a Participatory Action Research (PAR) approach involving 19 participants, including slaughterhouse workers and managers. Activities were conducted over three months, including needs assessment, halal regulation socialization, technical training, slaughter practice, development of Halal Product Assurance System (SJPH) documents, facility improvement, and certification mentoring.The results show measurable improvements. Participants’ knowledge increased from an average pre-test score of 52.3 to 81.6 in the post-test, and all participants obtained halal slaughterer training certificates. Two SJPH documents were successfully developed, including halal policies, SOPs, and monitoring forms. Facility improvements included the separation of clean and dirty areas, provision of sanitation equipment, and improved production flow. By the end of the program, two business units had applied for halal certification, and all participants met the initial administrative requirements